Pengaruh Faktor Tenaga Kerja Yang Dimoderasi Oleh Strategi Peningkatan Pengawasan Implementasi Keselamatan Kerja Terhadap Kecelakaan Kerja Di PT Semen Padang - Dainuri Dainuri; Sari Arlinda; Hendra Lukito (Jurnal Sehat Mandiri, 2020)
Occupational Health and Safety (K3) is one of the requirements to increase company productivity in order to be able to compete and survive in the era of globalization in the world free market economy. PT Semen Padang, as the largest industry in West Sumatra, is engaged in producing and trading cement, experiencing work accident problems. This study aims to determine the influence of internal and external labor factors moderated by the strategy of increasing the supervision of the implementation of work safety on work accidents at PT Semen Padang. The research method was a cross-sectional survey by interviewing 165 respondents who were selected by simple random sampling from a population of 423 people based on the formula of Issac and Michael. The results showed that the Variable Strategy for the Improvement of the Implementation of Work Safety Supervision (K3) was 0.019 <0.05, which means that the Strategy for Improving the Implementation of Safety Supervision had an influence on internal factors on work accidents. There is no significant effect on external factors with a value of 0.277> 0.05 on work accidents. The conclusion is that the better the internal and external factors in the workforce, the smaller the work accident rate. It is recommended that a supervisory program related to work stress and fatigue, supporting facilities and infrastructure and appropriate work tools be added to the OHS Supervision Improvement Strategy program.